Toward Octavio Paz : a reading of his major poems, 1957-1976 - Fein, John M., 1922-2015 (The University Press of Kentucky, 1986)
The undisputed intellectual leadership of Octavio Paz, not only in Mexico but throughout Spanish America, rests on achievements in the essay and in poetry. In the field of the essay, he is the author of more than twenty-five books on subjects whose diversity -- esthetics, politics, surrealist art, the Mexican character, cultural anthropology, and Eastern philosophy, to cite only a few -- is dazzling. In poetry, his creativity has increased in vigor over more than fifty years as he has explored the numerous possibilities open to Hispanic poets from many different sources.